Baby animals moving - Eszterhas, Suzi (Eszterhas, Suzi. Baby animals series., 2018)
"Around the world, baby animals move in different ways. Whether it's egret chicks practicing flapping their wings or zebra calves learning to run just a few hours after they're born, baby animals on the go are not only adorable-they can teach us about animal behavior, too. The second book in the Baby Animals series showcases twelve species from around the globe, each moving in different ways. Stunning photographs by award-winning wildlife photographer Suzi Eszterhas are paired with brief informational text. Back matter gives further information about Suzi and her wildlife photography work."--